Strategi Peningkatan Nilai Tambah Keripik Singkong sebagai Ekonomi Kreatif di Huta III Kampung Dolok Nagori Boluk, Kecamatan Bosar Maligas, Kabupaten Simalungun - Karisma Wardani; Khadijah Nur Aini; Prans Sintia Diadani; Reni Novianti Sari; Siti Aisyah (Lembaga Pengembangan Kinerja Dosen, 2026)
Micro, small, and medium enterprises (MSMEs), including those engaged in cassava chip production, play a significant role in the Indonesian economy. However, many MSMEs encounter difficulties in determining the factors that can support their success and designing strategies to remain competitive. This study explores the cassava chip producer “Nek Surati” through an analysis of marketing, technical, and operational aspects. The method used in this study is qualitative-descriptive with a case study approach involving in-depth interviews. The findings from this study indicate that the company has high sustainability potential, thanks to efficient product management, product variety, and operational efficiency. However, issues such as commodity price fluctuations and dependence on the harvest season remain challenges that need to be addressed. Strategies to overcome risks, including commodity inventory management and the development of digital marketing methods, were found to be the main solutions. With the implementation of risk management and optimization of marketing strategies, this business shows bright prospects for growth and contribution to the development of the Micro, Small, and Medium Enterprises sector.